2021
DOI: 10.1021/acsfoodscitech.1c00179
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-Ground Mango Kernel Powder: Characterization, LC-MS/MS Profiling, Purification of Antioxidant-Rich Gallic Acid, and Molecular Docking Study of Its Major Polyphenols as Potential Inhibitors against SARS-CoV-2 Mpro

Abstract: Mango processing waste (MPW) is an inexpensive and rich source of valuable substances. Hence, the mango kernel powder (MKP) from four cultivars (Chausa, Neelum, Barahmasi, and Dashehari) was characterized for the selection of the best cultivar. The MKP of the best cultivar (Dashehari) was analyzed for the profiling of polyphenols using LC-MS/MS in both modes of ionization (positive and negative) and indicated the presence of 50 compounds with specific retention times. After identification, gallic acid (GA), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Dwivedi et al’s docking and MD simulation confirmed their experimental results that holothurian sulfated glycans show potential effects against SARS-CoV-2 S protein RBD . Similar works include refs , , , and . Other studies applied experiments to identify potent compounds and used docking to reveal interactions. …”
Section: Methods and Approachesmentioning
confidence: 70%
“…Dwivedi et al’s docking and MD simulation confirmed their experimental results that holothurian sulfated glycans show potential effects against SARS-CoV-2 S protein RBD . Similar works include refs , , , and . Other studies applied experiments to identify potent compounds and used docking to reveal interactions. …”
Section: Methods and Approachesmentioning
confidence: 70%
“…Furthermore, mangiferin ( Figure 2 ), a hydroxy-xanthone glucoside, and the main active component in Mangifera indica , has previously shown to have broad-spectrum antiviral activity against a range of viruses including human immunodeficiency virus 1 (HIV-1) and herpes simplex virus type 1 (HSV-1). 16 , 17 More recently, mangiferin was identified as a potential inhibitor of the SARS-CoV-2 main protease (Mpro) in in silico studies, 18 and possess good pharmacokinetic properties, 19 , 20 suggesting inhibition of a conserved viral protein, valuable in the production of a broad-spectrum anti-coronavirus treatment. Further studies exhibited that mangiferin has significant binding affinity towards the spike glycoprotein of SARS-CoV-2 and ACE2 receptor and that it may be useful as a therapeutic and/or prophylactic agent for restricting viral attachment to the host cells.…”
mentioning
confidence: 99%